Identificação de áreas potencialmente contaminadas em ambientes urbanos - Rampanelli, Greice Barufaldi (2017)
Identifying and quantifying potentially contaminated areas allow proper management actions for such areas, contributing to a better urban planning in order to avoid human contact with contaminants. Unlike countries such as the United States, a few years ago Brazil started a reflection process and action management for these areas, including the application of methods to identify partially contaminated areas. Therefore, this research proposed to search for a method to identify potentially contaminated areas in urban environments. Hence, the work took place in four main steps. The first and second steps were performed by means of systematic literature review and were summed up to the analysis of international methods to identify and quantify potentially contaminated areas, as well asthe analysis of national methods to identify and quantify potentially contaminated areas. The third step included the compilation of information from the two previous steps, which resulted in a method. The fourth step involved the application of such method on an old area of the São Cristóvão neighborhood in the city of Passo Fundo, RS, Brazil, which is characterized by having several industries installed in the past, considering this is what mostly causes soil contamination. After analyzing the spreadsheets that presented all methods found, the one recommended by theEnvironmental Sanitation Technology Company of the State of São Paulo, Brazil (CETESB) was understood as the most adequate one, considering it presents a diversified identification process. The application of the method allowed identifying six potentially contaminated areas, whereas four of them correspond to old slaughterhouses and two of them to a metallurgical company, thus validating the applicability of the method selected.